Terminalia catappa aqueous leaf extract reverses insulin resistance, improves glucose transport and activates PI3K/AKT signalling in high fat/streptozotocin-induced diabetic rats - Franklyn Nonso Iheagwam; Olawumi Toyin Iheagwam; Michael Kemjika Onuoha; Olubanke Olujoke Ogunlana; Shalom Nwodo Chinedu (Scientific Reports, 2022)
Abstract Rising prevalence of type 2 diabetes mellitus (T2DM) in sub-Saharan Africa has necessitated surveys of antidiabetic medicinal plants. This study assessed the antidiabetic mechanism of Terminalia catappa aqueous leaf extract (TCA) in high fat/low dose streptozotocin-induced type 2 diabetic rats. T2DM was induced by a combination of high-fat diet and low dose STZ (30 mg/kg bw) and the animals were administered with TCA (400 and 800 mg/kg bw) orally daily for 28 days. Biochemical parameters and indices for diabetes including renal function tests and pancreatic histology were evaluated. Relative expression of hepatic insulin resistance, signalling and glucose transport genes were also assessed. Induction of T2DM resulted in significant (p < 0.05) weight loss, dysregulated glucose level and clearance, electrolyte imbalance and disrupted diabetic biochemical parameters. Diabetes onset also perturbed β-cell function and insulin resistance indices, damaged pancreas microanatomy, while disrupting the expression of insulin receptor substrate 1 (IRS-1), phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT) and glucose transporter isoform 4 (GLUT-4) mRNA. Oral treatment of diabetic animals with TCA significantly (p < 0.05) ameliorated alterations due to T2DM induction in a manner comparable with glibenclamide. These results suggest TCA exerts its antidiabetic action by reversing insulin resistance, improving glucose transport and activating PI3K/AKT signalling.